Color revolutions in Eurasia - Gerlach, Julia (SpringerBriefs in Political Science, 2014)
Why have large-scale protests and mass demonstrations in some post-socialist Eurasian states led to the fall of autocratic leaders, whereas similar other regimes prevail? This book addresses the question by providing an overview of eight cases of so-called Color Revolutions, and explains factors of 'success' and 'failure' by discussing the state-of-the-art in the political science discourse on Color Revolutions. It concludes by summarizing and contextualizing the results of the analysis and highlighting open research for political science on the theme of Color Revolutions.